A conceptual mechanistic model of amino acid fluxes in the small intestine, taking the example of pig - C.J.J. Garçon; N. Le Floc’h; Y. Mercier; J. van Milgen (Animal)
During digestion, almost 50% of absorbed essential amino acids (AAs) are metabolised by intestinal tissue, thus not appearing directly in the portal vein. This value, which is referred to as first-pass metabolism, seems high in relation to the overall efficiency of AA use considered in growth models. Experimental studies of first-pass metabolism are complicated due to the presence of numerous metabolic fluxes in the intestine and to the dynamics of digestion and absorption. The aim of this study was to integrate current knowledge of the metabolic AA fluxes in the small intestine in a conceptual model of intestinal AA metabolism. The model was built as a series of 200 intestinal segments, each having the same structure. Each segment was composed of seven pools, representing the fate of a generic AA according to their location (i.e., luminal or intestinal), origin (i.e., dietary or endogenous), and form (i.e., as protein or as a free AA). The pools were connected by fluxes, representing the main fates of AA, such as saturable transport of luminal AA or homeostasis of free or protein-bound AA in intestinal tissue. To parameterise the model, data from the literature were used, as well as values considered as reasonable. Simulations were carried out over 24 h, with five meals during the day and fasting during the night. Representing the small intestine as a series of segments allowed to account both for its tubular structure and for changing luminal environment. During the day, the model simulated the uptake of AA from the intestine and export to the blood, while during the night it simulated the uptake of AA from the blood to ensure intestinal homeostasis. Approximately, half of dietary AAs absorbed were metabolised in first-pass by intestinal tissue (i.e., used for intestinal protein synthesis). Part of this intestinal protein was secreted in the lumen as endogenous protein, which was driven by the presence of digesta, and endogenous protein can be digested and absorbed in more distal segments. In vivo, only the apparent first-pass metabolism of AA can be measured due to the dynamics of AA recycling and the tubular structure of the small intestine. This model can be a valuable tool for research and education to simulate the impact of nutrition on intestinal AA metabolism.